Evaluation of losartan plus hydrochlorothiazide combination therapy against amlodipine monotherapy in patients of hypertension - Sawant, Swati D.; Chawre, Sanjeevani M.; Dudhal, Kalpana S.; Bansode, Amit A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Microalbuminuria has been shown to predict cardiovascular disease (CVD) in patients with hypertension. Recently the FDC of losartan and hydrochlorothiazide (HCTZ) has been reported to be effective for achieving a target BP level and also improvement in cardiovascular prognosis. The present study was conducted to compare effect of losartan plus hydrochlorothiazide combination therapy and high dose amlodipine monotherapy on blood pressure and microalbuminuria. Methods: Total 184 patients with hypertension were randomly allocated to two groups. The patients in group 1 received Amlodipine 5 mg orally for first 4 weeks. The patients from group 2 received losartan 50 mg orally for first 4 weeks. Patients in group 1 were titrated to amlodipine 10 mg orally for next 4 weeks. The patients in group 2 were titrated to FDC of losartan (50 mg) plus HCTZ (12.5 mg) for next 4 weeks. Follow–up visits were scheduled at 4 weeks and 8 weeks. Pulse rate, sSBP and sDBP were estimated at each follow–up. Microalbuminuria was estimated at 8 weeks. Results: There was no significant difference in mean change in sSBP, sDBP and pulse rate between two treatment groups (p>0.05). There was greater reduction in microalbuminuria in group 2 patients (p<0.0001). The adverse effects such as flushing and lower extremity oedema were significantly more in amlodipine group (p<0.05). Conclusions: Losartan plus HCTZ has similar effect on BP, better safety profile and superior effect on microalbuminuria level reduction.